2019
DOI: 10.1007/s10854-019-00702-9
|View full text |Cite
|
Sign up to set email alerts
|

MOVPE growth conditions optimization for AlGaN/GaN/Si heterostructures with SiN and LT-AlN interlayers designed for HEMT applications

Abstract: In this work we present the influence of in situ deposited non-continous SiN layer and the chemical precursors III/V mole ratio change during GaN buffer growth for AlGaN/GaN/Si(111) heterostructures with low temperature AlN interlayer on their crystalline quality and electrical mobility of two dimensional electron gas (2DEG). We show, that application of SiN layer resulted in a decrease of (0002) full width at half maximum of diffraction peak below 400 arcsec and build-in stress in 2 µm thick heterostructures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The superior performances not only originate from these inherent material properties of GaN itself but also are related to the device technology based on AlGaN/GaN heterostructures. Because of the high mobility of the 2D electron gas (2DEG) formed at the AlGaN–GaN interface, a lateral device called a high-electron-mobility transistor (HEMT) offers tremendous potential for power switching and radiofrequency (RF) applications. , However, the large strain and defect at the AlGaN–GaN interface have become one of the main challenges for high-performance HEMT devices. Recent studies have shown that layer transfer technology would resolve the issue by controlling the 2DEG quality .…”
Section: Freestanding-membrane-based Electronicsmentioning
confidence: 99%
“…The superior performances not only originate from these inherent material properties of GaN itself but also are related to the device technology based on AlGaN/GaN heterostructures. Because of the high mobility of the 2D electron gas (2DEG) formed at the AlGaN–GaN interface, a lateral device called a high-electron-mobility transistor (HEMT) offers tremendous potential for power switching and radiofrequency (RF) applications. , However, the large strain and defect at the AlGaN–GaN interface have become one of the main challenges for high-performance HEMT devices. Recent studies have shown that layer transfer technology would resolve the issue by controlling the 2DEG quality .…”
Section: Freestanding-membrane-based Electronicsmentioning
confidence: 99%
“…Owing to the high mobility of 2D electron gas (2DEG) formed at the AlGaN/GaN interface, a lateral device called heterojunction field‐effect transistor (HFET), also known as high electron mobility transistor (HEMT), offers tremendous potential to the power switching and radio frequency (RF) applications. [ 9–11 ] To date, GaN‐based materials are generally heteroepitaxial grown on the foreign substrates of Si, sapphire, and silicon carbide (SiC) by metal‐organic chemical vapor deposition (MOCVD). [ 12–16 ] For power electronic applications, GaN HEMTs fabricated on Si substrate are the most usual structures owing to their cost‐effective large‐size wafer and conductive properties.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced drift velocity and higher breakdown field of GaN devices result in lower losses when the devices are operated at high voltage and temperature [4,5]. The existence of twodimensional electron gas (2DEG) at the interface of AlGaN/GaN in heterojunction field-effect transistor (HFET), also referred to as high electron mobility transistor (HEMT), presents immense potential for RF and power switching application [6].…”
Section: Introductionmentioning
confidence: 99%